Syrian «Chemical War» - V. А. Kovtun; D. P. Kolesnikov; M. V. Supotnitskiy; N. I. Shilo (Вестник войск РХБ защиты, 2023)
This article shows that the Syrian Arab Republic (SAR) was doomed for destruction by the «collective West» at least since 2002 within the framework of the process of fragmentation of the states of the Greater Middle East and bringing the Muslim Brotherhood to power in these countries. Later this process was called the Arab Spring. The analysis of the alleged «facts» of the use of chemical weapons by the Syrian Armed Forces made it possible to establish that they were nothing more than primitive artificial performances. No «chemical attack» in Syria, attributed to the Syrian army, pursued military objectives. The basic principles of the use of chemical weapons in combat were ignored. Not a single case of the use of factoryloaded chemical munitions has been recorded. Information attacks of the Western media and nongovernmental organizations, as well as their claims about the «Asad's regime»'s «chemical war against its own people» were carried out to support the Syrian antigovernmental forces at the time of their offensive on the governmentcontrolled territory, or when they were defeated by the Syrian army. Since 2013 the opposition has been practicing mass abductions and murders of children in order to obtain more convincing «pictures». But these crimes did not attract any attention of the Western governments or human rights organizations. The article also presents the evidence of systemic failures and shortcomings in the work of the OPCW UN Joint Investigative Mechanism (JIM) and the OPCW Fact Finding Mission (FFM), formed to establish the facts surrounding allegations of the use of toxic chemicals for hostile purposes in Syria. Considering staged fake chemical attack in Syria within the context of modern geopolitics, we can assume that it is possible to talk about the new «crusade» on Russia and its allies, but with the use of weapons of mass destruction. After the retrospective analysis of the mechanisms of information warfare, we may also note the deep intellectual degradation of its organizers in comparison with the similar information operations of the 1990s. This circumstance poses a serious threat not only to Syria and Russia, but to other countries as well, because the organizers of these operations are unable to assess even the immediate impacts of their actions.